2005
DOI: 10.2166/wst.2005.0651
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SAR (sodium adsorption ratio) between RO and NF processes for the reclamation of secondary effluent

Abstract: Secondary effluent reclamation and reuse has been considered as an alternative for agricultural irrigation water. Whilst all constituents in the reclaimed wastewater could affect plant growth and soil characteristics, the most important parameters for agricultural irrigation are salinity and SAR (Sodium Adsorption Ratio). Salinity affects the availability of crop water and sodium causes clay soils to disperse. Membrane technologies, especially NF (Nano-Filtration) and RO (Reverse Osmosis), have played in a key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…In the examples listed in Table 1, the Na to (Ca + Mg) ratio of NF concentrate from the Rio Grande return fl ow [5] decreased from 1.47 to 0.65. Likewise, the Cl to SO 4 ratio of the municipal effl uent studied by Chang et al [4] decreased from 2.28 to 0.85. Salinity of irrigation water will inevitably increase upon application of NF concentrates to irrigation water stream.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the examples listed in Table 1, the Na to (Ca + Mg) ratio of NF concentrate from the Rio Grande return fl ow [5] decreased from 1.47 to 0.65. Likewise, the Cl to SO 4 ratio of the municipal effl uent studied by Chang et al [4] decreased from 2.28 to 0.85. Salinity of irrigation water will inevitably increase upon application of NF concentrates to irrigation water stream.…”
Section: Introductionmentioning
confidence: 83%
“…Since NF concentrates are enriched with divalent ions, some suggest that its application to irrigation stream would not be deleterious, or can be even benefi cial, as low SAR improves soil structure [15]. However, as discussed in the introduction, the SAR of NF concentrates is not substantially lower than that of the feed water, although it is lower than that of RO concentrates [2,4,5,14,16]. In addition, the formation of sulfate ion pairs with divalent cations further reduces the replacement of exchangeable Na from the cation exchange sites [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of Oron et al (2008) showed an electro conductivity (EC) removal Table 1 -Cost and benefit of wastewater reuse (Fan et al, 2013 can remove sodium ions and divalent cations, and thus it is very effective for the decline of sodium adsorption ratio (SAR). Chang et al (2005) found a SAR removal of 61% was observed for an initial SAR of 1.8 with the use of RO. For disinfection namely the removal of pathogens, the recommended technology by several guidelines is ultraviolet treatment .…”
Section: Wastewater Reclamation Technologymentioning
confidence: 91%
“…Sodium (Na + ), chloride (Cl À ), and boron are the ions of most concern among the specific toxic ions. Salinity directly affects the availability of crop water, while sodium causes clay soil to disperse (Chang et al, 2005). A limit on sodium content is not included in the 2006-MWE standards, while chloride limits are not included in either the previous or the 2006-MWE standards.…”
Section: Specific Ion Toxicity and Water Infiltration Ratementioning
confidence: 99%